SUFISM AND MYSTICISM IN AHMAD YASSAWI’S SUFI DOCTRINE (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The article scientifically analyzes the unique ways of achieving the perfection of Sufism in the Sufi teaching of Ahmed Yassawi. Sufism and its ideas, especially the idea of a perfect man, have interested people since the very beginning of Sufism. Many scientists have studied this teaching, expressed their opinions and contributed to its development. Especially in the development of this teaching contributed the Central Asian mystics: Yassawi, Najmuddin Kubro, Ghazali, Abdukholik Gijduvani, Aziziddin Nasafi and others.